Deep learning for diagnosis of COVID-19 using 3D CT scans. (May 2021) - Serte, Sertan; Demirel, Hasan
Abstract: A new pneumonia-type coronavirus, COVID-19, recently emerged in Wuhan, China. COVID-19 has subsequently infected many people and caused many deaths worldwide. Isolating infected people is one of the methods of preventing the spread of this virus. CT scans provide detailed imaging of the lungs and assist radiologists in diagnosing COVID-19 in hospitals. However, a person's CT scan contains hundreds of slides, and the diagnosis of COVID-19 using such scans can lead to delays in hospitals. Artificial intelligence techniques could assist radiologists with rapidly and accurately detecting COVID-19 infection from these scans. This paper proposes an artificial intelligence (AI) approach to classify COVID-19 and normal CT volumes. The proposed AI method uses the ResNet-50 deep learning model to predict COVID-19 on each CT image of a 3D CT scan. Then, this AI method fuses image-level predictions to diagnose COVID-19 on a 3D CT volume. We show that the proposed deep learning model provides 96 % AUC value for detecting COVID-19 on CT scans. Highlights: We propose a new AI system to estimate COVID-19 on the images of a person's 3D CT volume. The proposed AI system builds on ResNet-50 to obtain predictions on 3D CT volume CT images. The proposed AI system employs the ResNet-18 model in conjunction with the majority voting. The proposed AI system employs the ResNet-50 model in conjunction with the majority voting.